Plan showing the positioning of the New England Medical Center, ca. 1969 - The Architects Collaborative, INC. (Tufts Archival Research Center, 2005)
5x7; title attached to photo: "Medical Center at hinge point in Boston commercial spine, with the new Government Center to the north and the Prudential Center to the west."